The economics of immense risk, urgent action and radical change: towards new approaches to the economics of climate change. Issue 3 (3rd July 2022) - Stern, Nicholas; Stiglitz, Joseph; Taylor, Charlotte
ABSTRACT: Designing policy for climate change requires analyses which integrate the interrelationship between the economy and the environment. We argue that, despite their dominance in the economics literature and influence in public discussion and policymaking, the methodology employed by Integrated Assessment Models (IAMs) rests on flawed foundations, which become particularly relevant in relation to the realities of the immense risks and challenges of climate change, and the radical changes in our economies that a sound and effective response require. We identify a set of critical methodological problems with the IAMs which limit their usefulness and discuss the analytic foundations of an alternative approach that is more capable of providing insights into how best to manage the transition to net-zero emissions.